Ätiologie und Pathophysiologie des Fibromyalgiesyndroms - Sommer, Claudia; Wang, Haili (Der Schmerz, 2012)
Background: The scheduled update to the German S3 guidelines on fibromyalgia syndrome (FMS) by the Association of the Scientific Medical Societies (“Arbeitsgemeinschaft der Wissenschaftlichen Medizinischen Fachgesellschaften”, AWMF; registration number 041/004) was planned starting in March 2011.Materials and methods: The development of the guidelines was coordinated by the German Interdisciplinary Association for Pain Therapy (“Deutsche Interdisziplinären Vereinigung für Schmerztherapie”, DIVS), 9 scientific medical societies and 2 patient self-help organizations. Eight working groups with a total of 50 members were evenly balanced in terms of gender, medical field, potential conflicts of interest and hierarchical position in the medical and scientific fields. Literature searches were performed using the Medline, PsycInfo, Scopus and Cochrane Library databases (until December 2010). The grading of the strength of the evidence followed the scheme of the Oxford Centre for Evidence-Based Medicine. Results: Current data do not identify distinct etiologic or pathophysiological factors mediating development of FMS. The development of FMS is associated with inflammatory rheumatic diseases (EL2b), with gene polymorphisms of the 5-hydroxytryptamine (HT)2 receptor (EL3a), lifestyle factors (smoking, obesity, lack of physical activity; EL2b), physical and sexual abuse in childhood and adulthood (EL3a). Conclusion: FMS is most likely the result of various pathogenetic factors and pathophysiological mechanisms.The English full-text version of this article is available at SpringerLink (under “Supplemental”).